The Effect of Implementing Project Based Learning on the Problem Solving Ability of Class X Students in Economics Learning at MAN - Rismayanti; Tawe, Amiruddin; Sahabuddin, Romansyah; Supatminingsih, Tuti; Najamuddin; Haryoko, Sapto (PT. Maju Malaqbi Makkarana, 2024)
This study aims to, 1) analyze the differences in problem-solving skills between students who are given treatment in the form of applying the Project Based Learning model with students who are given a conventional model in Economic Learning at MAN Jeneponto, 2) to analyze the effect of applying Project Based Learning on the problem-solving skills of class X students in economic learning at MAN Jeneponto. The research method used is quasi-experiment with Nonequivalent (Pretest and Posttest) Control Group Design. Data collection methods are through tests (pretest and posttest), questionnaires, and documentation. The number of samples in this study were 76 students, where in the experimental class there were 38 students and in the control class 38 students. The data analysis used is the N-Gain of the experimental class and control class, as well as the experimental class Hypothesis test. The results of this study indicate that the N-Gain of the experimental class is in the high and effective category, while the control class is in the low and less effective category. This means that the application of Project Based Learning is effective on the problem solving skills of class solving ability of class X students in economic learning at MAN Jeneponto